2023
DOI: 10.1007/jhep06(2023)105
|View full text |Cite
|
Sign up to set email alerts
|

Holographic thermodynamics of rotating black holes

Abstract: We provide mass/energy formulas for the extended thermodynamics, mixed thermodynamics, and holographic conformal field theory (CFT) thermodynamics for the charged and rotating Kerr-Newman Anti-de Sitter black holes. Then for the CFT thermal states dual to the black hole, we find the first-order phase transitions and criticality phenomena in the canonical ensemble with fixed angular momentum, volume, and central charge. We observe that the CFT states cannot be analogous to the Van der Waals fluids, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It is important to know that positive mass indicates stable BH, whereas negative mass indicates towards the instability of the BH. There are several approaches to calculating the mass of a black hole like the conformal approach [52][53][54], by using the first law of thermodynamics [55,56]. Here, we calculate the geometric mass by setting f (r) = 0 [57,58].…”
Section: Physical Existence Of the Rindler-schwarzschild Black Holementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to know that positive mass indicates stable BH, whereas negative mass indicates towards the instability of the BH. There are several approaches to calculating the mass of a black hole like the conformal approach [52][53][54], by using the first law of thermodynamics [55,56]. Here, we calculate the geometric mass by setting f (r) = 0 [57,58].…”
Section: Physical Existence Of the Rindler-schwarzschild Black Holementioning
confidence: 99%
“…In the coming discussions, we calculate the other thermodynamic properties of BHs using this corrected entropy and compare the results by setting γ = 0 for no correction and γ = 1 for correction terms. Now, we determine the thermodynamic temperature T by using the first law of thermodynamics[55,72]:…”
mentioning
confidence: 99%
“…The holographic interpretation of charged AdS black holes is intriguing in this new paradigm where Newton's constant is the dynamics parameter. Central charge criticality studies for non-linear electromagnetic black holes [29,30], Gauss-Bonnet black holes [31,32], and other types of black hole studies [33,34] have all shown that this transition is determined by the degrees of freedom of its dual field theory in the large N limit. As a consequence of the G N variation, the first law (1.1) can be reformulated in the following manner:…”
Section: Introductionmentioning
confidence: 99%